Risk Mitigation – What’s Your Score? - Crosby, Philip (Juniper Publishers, 2018)
This article examines conventional methods for risk identification and risk scoring using ‘look-up’ tables, and concludes that such methods are inherently flawed and offer false confidence in project management. The author suggests a series of searching questions to test the efficacy of traditional risk assessment in order to better prepare the project for review. Important further considerations are posed in relation to non-specific, irrational risk exposure (i.e. Black Swans), and the author presents two approaches for improved preparedness against undefined risk.